2021
DOI: 10.30629/0023-2149-2021-99-2-91-97
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical predictors of arterial hypertension

Abstract: Arterial hypertension (AH) remains one of the most common diseases and a leading risk factor for cardiovascular diseases (CVD) in the 21st century. It determines the importance of a search for new factors provoking an increase in blood pressure. This review focuses on studies of preclinical predictors of hypertension. Orthostatic circulatory disorders with clinical signs of cardiovascular deconditioning are risk factors for the development of hypertension and CVD, accompanied by a more rapid increase in vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Asymptomatic orthostatic disturbances (“rise” and “drop”) can be defined as preclinical OHT and OH. Orthostatic changes with a ΔSBP of ±5 mmHg that were accompanied by a minimal risk of developing AH could be defined as orthostatic normotension (ONT) [ 22 ]. This terminology emphasizes the theoretical possibility that preclinical OH and OHT can potentially evolve into clinical disorders (OH and OHT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymptomatic orthostatic disturbances (“rise” and “drop”) can be defined as preclinical OHT and OH. Orthostatic changes with a ΔSBP of ±5 mmHg that were accompanied by a minimal risk of developing AH could be defined as orthostatic normotension (ONT) [ 22 ]. This terminology emphasizes the theoretical possibility that preclinical OH and OHT can potentially evolve into clinical disorders (OH and OHT).…”
Section: Discussionmentioning
confidence: 99%
“…This protocol allowed the results of orthostatic circulatory regulation to be assessed, irrespective of the effect of the individual’s height (hydrostatic pressure). Given the higher prevalence of AH in African countries compared to European countries, it was important to explore possibilities for the early detection of preclinical orthostatic abnormalities [ 22 ] and their racial differences using the new HUTT test to assess young healthy European and African adults.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to clinical orthostatic abnormalities, the association of preclinical abnormalities with vascular stiffening remains poorly understood [25,26]. Nevertheless, it has been shown that orthostatic abnormalities corresponding to preclinical OHT significantly increase the risk of AH in a young population under 30 years of age [27], and preclinical OH increases the risk of AH in a population over 45 years of age [28].…”
Section: Clinical Orthostatic Hypotension (Oh) and Clinical Orthostat...mentioning
confidence: 99%